Curcumin in heart failure: A choice for complementary therapy?. (May 2018) - Saeidinia, Amin; Keihanian, Faeze; Butler, Alexandra E.; Bagheri, Ramin Khameneh; Atkin, Stephen L.; Sahebkar, Amirhossein
Graphical abstract: Abstract: Heart failure is a major public health concern and one of the most common reasons for a cardiac hospital admission. Heart failure may be classified as having a reduced or preserved ejection fraction and its severity is based on the symptom score. Given the aging population, it is predicted that admissions with heart failure will increase. Whilst pharmacological therapy has improved the associated morbidity and mortality, there is a need for additional therapies to improve the clinical outcome as the death rate remains high. Curcumin is a natural product derived from turmeric that appears to have cardiovascular benefit through a number of mechanisms. In this review, we have assessed the mechanisms by which curcumin may exert its effects in different models of heart failure and show that it has promise as a complementary treatment in heart failure.